Reinterpreting Hadiths Prohibiting Depiction of Living Beings through Gadamerian Hermeneutics in the Avatar Da'wah Trend - Zubeir Ahmad Nasution; Lilia Ulya Amalia; Muhammad Fitriyadi; Agustiar; Akrimi (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article reexamines the hadith prohibiting the depiction of living creatures within the contemporary digital da'wah landscape, which increasingly relies on visual representation, particularly through the use of avatars. This hadith has often been understood textually and ahistorically, creating tension between religious norms and modern digital communication practices. This study examines the construction of the normative meaning of the hadith prohibiting drawing within the historical context of early Islam and how this meaning can be reinterpreted and contextualized within contemporary visual da'wah practices through the hermeneutical approach of Hans-Georg Gadamer. The method employed a qualitative approach based on library research, examining thematic hadiths, classical and modern scholarly commentary, and philosophical hermeneutics literature. The analysis is conducted through a hermeneutic dialogue between the text's horizon and the contemporary reader, emphasizing the historical-affective consciousness and the fusion of horizons. The study's results reveal that the prohibition served as a theological mechanism to maintain the purity of monotheism in early Islamic societies that still tended toward the cult of visual symbols. The use of avatar images in digital da'wah can be understood as a functional and communicative representational medium, not as a theological expression, as long as it does not contain elements of glorification or deviation from the creed. The novelty lies in the application of Gadamer's hermeneutics as an analytical framework to bridge the normative authority of hadith with the practice of avatar-based visual da'wah. These findings strengthen the methodology of hadith contextualization in addressing the dynamics of digital visual culture.